2010
DOI: 10.1073/pnas.1001576107
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic expression of CBBP, a CXC domain protein, establishes paramutation in maize

Abstract: Paramutation is the ability of specific DNA sequences to communicate in trans to establish meiotically heritable expression states. Paramutation at the maize b1 locus is mediated by seven unique noncoding transcribed tandem repeats of 853 bp that are required to establish and maintain the meiotically heritable expression and distinct chromatin states associated with b1 paramutation. In this study, we report the identification of a CXC-domain protein CBBP (CXC domain b1-repeat binding protein) that binds to a d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 23 publications
0
27
0
Order By: Relevance
“…Although the B′* state established by the transgene is not as paramutagenic as "natural" paramutation, it is similar to that observed for B′ alleles with fewer repeats (20), the state established by the binding of the CBBP protein (11), and most other paramutation systems, which are often not 100% efficient (46). Thus, the generation of a hairpin dsRNA or siRNAs from the b1TR sequence can establish a heritable chromatin state in trans at the endogenous locus.…”
Section: Discussionmentioning
confidence: 76%
“…Although the B′* state established by the transgene is not as paramutagenic as "natural" paramutation, it is similar to that observed for B′ alleles with fewer repeats (20), the state established by the binding of the CBBP protein (11), and most other paramutation systems, which are often not 100% efficient (46). Thus, the generation of a hairpin dsRNA or siRNAs from the b1TR sequence can establish a heritable chromatin state in trans at the endogenous locus.…”
Section: Discussionmentioning
confidence: 76%
“…Perhaps the CTR of RMR2 directs nucleic acid binding, while the poorly conserved N-terminal region coordinates contacts with other peptides. These speculative assignments remain to be tested, but interestingly, a DNA binding protein associating with the B1-I upstream repeats appears to play a role in facilitating paramutation at b1 (Brzeska et al, 2010). In A. thaliana, a DNA binding protein (SSH1/DTF1) required for both DNA methylation-dependent and methylation-independent gene silencing (Liu et al, 2011) was recently found in coimmunoprecipitations with NRPD1 (Law et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…This interaction was mapped to a specific domain in CLF, the CXC domain, found in a number of other plant proteins. Although the function of this domain has not been extensively characterized, a CXC protein within the maize protein CBBP, that has a role in paramutation, was found to mediate DNA binding (Brzeska et al 2010).…”
Section: Prc2 Recruitment and Lncrnas In Other Organismsmentioning
confidence: 99%